RESPON SAREKAT ISLAM TERHADAP KEBIJAKAN PENDIDIKAN PEMERINTAH KOLONIAL BELANDA (1905-1933) - Dwi Lestari (JSI: Jurnal Sejarah Islam, 2022)
In the early 20th century, education experienced many polemics due to the policies of the Goeroe Ordinance and the Illegal Schools Ordinance. In 1922, for the first time the Goeroe Ordinance met resistance from the Sarekat Islam. And then this organization became a pillar of resistance for the people. This study uses the theory of "Challenge and Response" Arnold J. Toynbee and the theory of Public Policy. While the method used is a historical research method. The results of this study indicate that the background of the issuance of the Goeroe Ordinance is due to past trauma to the power of Islam. Therefore, this ordinance provides more control over Islam, especially among religious teachers. Meanwhile, the Illegal Schools Ordinance was issued after the outbreak of private schools due to the economic crisis. Activities carried out by Sarekat Islam in dealing with these policies included holding the Al-Islam I Congress, publishing manifestos, and holding general actions in all PSII afdeling areas.